Criminal Liability Of Perpetrators Of Illegal Medical Practices (Perspective Of Law Number 17 Of 2023 Concerning Health) - Muhammad Reski Ansyah; Abdul Razak Nasution (ASIAN PUBLISHER, 2023)
In connection with this, Legislation in the Health Sector was made. Based on Article 1 paragraph (1) of Permenkes No. 2052/MenKes/Per/X/2011 concerning Practice Permits and Implementation of Medical Practices,